EFFECT OF PROLACTIN AND TESTOSTERONE LEVELS ON SEMEN PARAMETERS OF MEN WITH PRIMARY AND SECONDARY INFERTILITY (American Journal of Interdisciplinary Research and Development, 2023)
The regular interactions and balance of the relationship of prolactin, gonads and testicular hormones and their suitability ensure that the sperm is normal in males. So this study is an attempt to classify male infertility depending on WHO criteria of seminal changes and to evaluate serum Prolactin, Testosterone FSH and LH levels in the participants, also determine the association between serum Prolactin, Testosterone levels and  subtypes of male infertility. This study involved three hundred  infertile males having infertility more than one year (cases group) and three  hundred  age-matched fertile males with definite paternity in past two  years (control group) were included to the study from Jan  2020 -Dec 2021 at Al-Kut Hospital, Infertility Center in the Alkut city. Serum levels of hormones were measured by electrochemiluminescense immunoassay technique. Approximately half of patient's age ranged between 30- 39 years. Sixty eight percentage of cases complained from primary infertility. About 71.3% of patients had infertility duration between 1 - 5 years. This percentage decreased with increasing the infertility years. Most common infertile group was Asthenospermia (34.3%). A higher significant levels of serum Prolactin, FSH and LH found in cases than controls (p